Analysis of educational resilience among Costa Rican students using data from the PISA 2009 reading assessment - Fernández Aráuz, Andrés (2013)
This article analyzes the Costa Rican students identified as “resilient” in the PISA 2009 evaluation; and compares them to their peers that, despite having similar socioeconomic background, obtained poorer results in this test. The article shows that differences in performance may be associated with the use of better reading comprehension strategies, personal interest in reading and the student's attitude towards school.